Towards a typology of logistics "work" beyond formal employment: a synthesised literature review - Wang, Xueqin (2024)
Purpose: Logistics at work is rapidly changing. The changing trend is especially prominent when considering the active involvement of individuals that perform diverse forms of formal/informal “logistics work” (e.g. crowd logistics and self-collection). Thus, by conducting a synthesised review (n = 55), this study aims to provide a typology of individuals' logistics work. Design/methodology/approach: The total social organisation of labour is used as a guiding framework. A deductive literature analysis is performed based on the identified journal articles. Findings: The review findings reveal three major contexts where individuals perform logistics work: formal organisation, social community and private household, with a decreased level of formality. Under each context, individuals may be engaged in paid or unpaid activities, creating six forms of logistics work, termed as paid/voluntary professional logistics, incentivised/friendly social logistics and rewarded/free consumer logistics. Furthermore, an actor–sphere–resource–value conceptualisation of individual logistics is proposed, focussing on the chains of actors, work settings, resource input and value outcome. Originality/value: The results provide a theoretical foundation for further research in individual- or consumer-centrism in logistics. Two research directions and seven research questions are presented for future investigation.